2001
DOI: 10.1093/brain/124.10.2098
|View full text |Cite
|
Sign up to set email alerts
|

Pain and the body schema: Evidence for peripheral effects on mental representations of movement

Abstract: Some accounts of body representations postulate a real-time representation of the body in space generated by proprioceptive, somatosensory, vestibular and other sensory inputs; this representation has often been termed the 'body schema'. To examine whether the body schema is influenced by peripheral factors such as pain, we asked patients with chronic unilateral arm pain to determine the laterality of pictured hands presented at different orientations. Previous chronometric findings suggest that performance on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
195
9
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(238 citation statements)
references
References 28 publications
21
195
9
3
Order By: Relevance
“…Patients have longer reaction times when the hand, which must be mentally rotated, corresponds to the limb in pain [45], in agreement with evidence for anatomical 'constraints' during mental rotation of body parts [39]. Inflow in this context refers to initial sensory information conveying sensation and proprioception [44] rather than muscular inflow [22,23].…”
Section: Introductionsupporting
confidence: 58%
“…Patients have longer reaction times when the hand, which must be mentally rotated, corresponds to the limb in pain [45], in agreement with evidence for anatomical 'constraints' during mental rotation of body parts [39]. Inflow in this context refers to initial sensory information conveying sensation and proprioception [44] rather than muscular inflow [22,23].…”
Section: Introductionsupporting
confidence: 58%
“…After prism adaptation, visual body midline judgments erred in the opposite direct, towards the side of the unaffected side [35]. In contrast to previous studies [5][6][7]16,24,25,34], these latter experiments [35,36,38] demonstrated that the side for which there is a diminished representation of space does not always correspond to that of the affected limb.…”
Section: An Impaired Perception Of Space Not Limited To the Side Of Tmentioning
confidence: 57%
“…pain, swelling and skin changes in the affected limb, some of these patients tend to ignore or have an altered mental representation of the affected limb (somatoparaphrenia); movements are smaller and less frequent (hypokinesia), and take conscious effort [5][6][7]16]. They have difficulties recognizing their own limb [24] and estimating its position [17], its size [25] and its orientation [34].…”
Section: An Impaired Body Representation In Crpsmentioning
confidence: 99%
“…The use of motor imagery strategies in mental rotation of hands has been corroborated by many authors [e.g., 9,14,23]. Evidence for motor imagery being involved in mental rotation of body parts comes from clinical cases [e.g., 3,4,12,16] and from neuroimaging studies (see [22] for review). Further studies proposed that mental rotation tasks can be solved by different strategies, involving visual imagery or motor imagery [2,11], and that the choice of strategy might depend on the type of stimuli [21] or the instructions [20].…”
Section: Introductionmentioning
confidence: 88%